The impact of corruption on economic growth in developing countries and a comparative analysis of corruption measurement indicators - Eleftherios Spyromitros; Minas Panagiotidis (Cogent Economics & Finance, 2022)
Although corruption has attracted researchers' attention for more than 30 years, it remains one of the most significant political challenges all countries face. Even though corruption measures have improved, they lack reliability and clarity. Two aspects of corruption are examined in this paper: a) its measurement and b) its effects on the economic performance of 83 developing countries in the period 2012-2018 with AR (1) and FM-OLS data processing techniques. It provides an extensive reference for and critical assessment of different corruption index approaches, focusing on the already known and widespread indicators. Furthermore, it refers to the measures most suited for statistical analyses regarding perceptions and experiences. In addition, the study's empirical results show that corruption hinders the economic growth of those developing countries. Different levels of corruption impact economic growth in different regions; specifically in Latin American countries, corruption impacts positively on economic growth or vice versa; in the other regions, it is negative. Finally, investment, human development, government growth, and institutional quality play essential roles in economic growth.
Keywords: C23; D73; E60; O4; R11; 330; Corruption indexes; economic growth; governance; perception; regional analysis